Hyaluronic acid auto-crosslinked polymer (ACP): Reaction monitoring, process investigation and hyaluronidase stability. (4th October 2016) - Pluda, Stefano; Pavan, Mauro; Galesso, Devis; Guarise, Cristian
Abstract: Hyaluronic Acid (HA) is a non-sulphated glycosaminoglycan that, despite its high molecular weight, is soluble in water and is not resistant to enzymatic degradation, the latter of which hinders its wider application as a biomedical material. Auto-crosslinked polymer (ACP) gels of HA are fully biocompatible hydrogels that exhibit improved viscoelastic properties and prolonged in vivo residence times compared to the native polymer. Crosslinking is achieved through a base-catalysed reaction consisting of the activation of HA carboxyl groups by 2-chloro-1-methylpyridinium iodide (CMPI) and subsequent nucleophilic acyl substitution by the hydroxyl groups of HA in organic solvent. In this study, a number of ACP hydrogels have been obtained via reactions using varying ratios of CMPI to HA. The crosslinking reaction was monitored by rheological measurements in organic solvents during CMPI addition to the reaction mixture. The ACP intermediates, powders and hydrogels were characterized, helping to elucidate the crosslinking process. A two-step mechanism was proposed to explain the observed trends in viscosity and particle size. Syntheses were carried out by varying the reaction temperature, respectively at 0 °C, 25 °C and 45 °C in N-Methyl-2-Pyrrolidone (NMP), as well as the solvent respectively in NMP, DMSO and DMF at 25 °C. Interestingly, varying these parameters did not substantially affect the degree of crosslinking but likely did influence the intra/inter-molecular crosslinking ratio and, therefore, the viscoelastic properties. A wide range of crosslinking densities was confirmed through ESEM analysis. Finally, a comparative hyaluronidase degradation assay revealed that the ACPs exhibited a higher resistance toward enzymatic cleavage at low elastic modulus compared to other more chemically resistant, crosslinked HAs. These observations demonstrated the importance of crosslinking density of matrix structures on substrate availability. Graphical abstract: Highlights: Synthesis of Auto cross-linked Polymer (ACP) monitored by rheological analysis. Relationship between viscoelastic and morphological properties of cross-linked HA. A two-step mechanism fits the observed trends in viscosity and particle size. The effect of solvent and temperature during the ACP synthesis were investigated. ACPs exhibited a higher hyaluronidase resistance compared to other crosslinked HAs.